Implementação do roteiro didático metaprocedimental numa turma de ensino médio: eficiência, eficácia e reverberações - Bezerra, Thárcila Ellen Aires (2021)
In this work, we analyze the written and oral reports referring to the literary reading carried out by two classes of the 3rd year of High School at the integral school Lyceu Paraibano, located in the city of João Pessoa-PB, in the context of didactic sequences elaborated, organized and implemented by the author of this research, on December 2, 2019. This actyion aimed to analyze, by the use of the Meta-procedural Didactic Script (RDM), the development of the fictionalization process in students’ literary reading, through reports of their aesthetic experience with the text. This instrument was produced and tested by the Programs CANAL 67 (Cinema Articulated to the Notions of Literary Anthropology, sixth and seventh arts) and PARDAL (Program for the Application of the Meta-procedural Didactic Script in Literary Anthropology) that included PIBIC, PROLICEN and PROBEX projects at the Federal University of Paraíba, in the years 2015 to 2019. It is an instrument theoretically based in the thought of the German critic Wolfgang Iser for the act of fictional reading. In order to achieve the presented purpose, our specific objectives consisted of: selecting two high school classes, one entitled Control Group (CG), and the other, Treatment Group (GT); observing the method used by the teacher to teach literary reading; choosing a short film and a short story, together with the teacher, considering the Iserian concept of Repertoire and the Vygotskian concept of Zone of Proximal Development (ZDP) of the students; planning teaching sequences with and without the use of the RDM; implementing the sequences; evaluating their productions in the light of the theoretical framework; and comparing the results. On the scheduled day, we performed experiences of presentation and meaning in both groups, aiming at the sharing of reading by the students and the presentation of the participants. The difference was as follows: in the GT we exhibited the short film The Maker (KEZELOS, 2015), analyzed verbally and together, following the proposal of the RDM. Afterwards, we read the short story The game, by Osman Lins (2003 [1957]) and asked the students to also analyze it, but this time, in writing. In the CG, the short story and the Script were not used. The written productions should report the students’ experiences and perceptions in relation to the short story. In summary, we developed two studies: one with the GC, which did not receive mediation guided by the RDM, and another, with the GT, the one in which the RDM was used. We compared the results obtained, which allowed us to demonstrate that in the Treatment Group there was a greater detail of the students’ reading processes. Thus, we infer that the use of the RDM contributed to the development of the fictionalization process in literary reading of the students participating in the present study. These results enabled, therefore, the proof of the effectiveness and efficiency of the RDM, as well as the discussion of its possible methodological and theoretical reverberations.